Demographic Changes in Latin America : The Good, the Bad and ... - Acosta Ormaechea, Santiago (IMF Working Papers; Working Paper ;, 2017)
The paper develops a simple, integrated methodology to project public pension cash flows and healthcare spending over the long term. We illustrate its features by applying it to the LAC5 (Argentina, Brazil, Chile, Colombia and Mexico), where public spending pressures are expected to increase significantly over 2015-50 due to demographic trends and rising healthcare costs. We simulate alternative pension reforms, including the transition from a defined benefit to a defined contribution pension system and the fiscal burden of a minimum guaranteed pension under the latter. We also analyze public healthcare outlays in the LAC5, which is likewise expected to increase significantly over 2015-50 due to aging and the so-called excess cost growth factor of healthcare services, showing that curbing the evolution of the latter (e.g., through enhanced competition in the healthcare sector) could aid in containing spending pressures. Despite its simplicity, the methodology yields projections that compare well with other approaches. It therefore provides a good benchmark for assessing alternative reform scenarios, particularly in data-constrained countries.